Social Return on Investment: What is and How far has been Researched? - Maliha, Hasna (Islamic Social Finance, 2024)
This study aims to examine the development of research on the topic "Social Return on Investment" and to identify potential research agendas based on journals published on this theme. The research employs a qualitative method with a bibliometric analysis approach. The data used is secondary data on the theme "Social Return on Investment" from the Scopus database, comprising 466 journal articles. The data was then processed and analyzed using VosViewer software to map the bibliometric development of "Social Return on Investment" research globally. The study found 4 clusters with the most frequently used keywords being social return on investment, investment, human, humans, social value, social impact, and cost-benefit analysis. Subsequently, research path topics related to Social Return on Investment are SROI for Sustainable Development, SROI in Health Economics, SROI and Social Well-being, and SROI through Economic Evaluation.